2023
DOI: 10.1177/00110000231170310
|View full text |Cite
|
Sign up to set email alerts
|

Asian American Men’s Gendered Racial Socialization and Fragmented Masculinity: Interpretive Phenomenological Analysis

Brian TaeHyuk Keum,
Lydia HaRim Ahn,
Andrew Young Choi
et al.

Abstract: We investigated the messages, ideals, and critical experiences that constitute gendered racial socialization for Asian American men (AAM) throughout their development. We employed interpretive phenomenology to analyze interview data from 15 sociodemographically diverse AAM. We identified seven themes: (a) intergenerational parental ideologies, (b) geographic and neighborhood influences, (c) multilevel gendered racism, (d) silencing of gendered racial experiences, (e) survival by identity erasure, (f) rare expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Some studies documented other ERS strategies in AAPI families, such as egalitarianism (French et al, 2013;Kiang et al, 2022;Kim, Hunt, et al, 2023;Patel et al, 2022), pluralism (Kiang et al, 2022;Kim, Hunt, et al, 2023;Ren et al, 2022), minimization of race (Keum et al, 2023;Kiang et al, 2022;Kim, Hunt, et al, 2023), exposure to diversity (Alvarez et al, 2006;Park, 2020;Tian, 2023), avoidance of race talk (Keum et al, 2023) ERS with other constructs: discrimination (Ajayi & Syed, 2014), ethnic-racial identity (Wu et al, 2020;Xie et al, 2021), American identity (Wu et al, 2020), and model minority experiences (Kiang et al, 2019;Xie et al, 2021).…”
Section: Extent and Nature Of Ersmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies documented other ERS strategies in AAPI families, such as egalitarianism (French et al, 2013;Kiang et al, 2022;Kim, Hunt, et al, 2023;Patel et al, 2022), pluralism (Kiang et al, 2022;Kim, Hunt, et al, 2023;Ren et al, 2022), minimization of race (Keum et al, 2023;Kiang et al, 2022;Kim, Hunt, et al, 2023), exposure to diversity (Alvarez et al, 2006;Park, 2020;Tian, 2023), avoidance of race talk (Keum et al, 2023) ERS with other constructs: discrimination (Ajayi & Syed, 2014), ethnic-racial identity (Wu et al, 2020;Xie et al, 2021), American identity (Wu et al, 2020), and model minority experiences (Kiang et al, 2019;Xie et al, 2021).…”
Section: Extent and Nature Of Ersmentioning
confidence: 99%
“…Coard et al (2023) found that some but not all parents felt that personal testimonies of their own experiences of discrimination were a necessary part of preparation for bias. Several studies documented how family socialization occurs in combination with other actors (e.g., peers, media) and other settings (e.g., community contexts, school) (Ahn et al, 2022;Keum et al, 2023;Lee et al, 2022;Sladek et al, 2022). Ahn et al (2022) and Keum et al (2023) examined gendered racial socialization among women and men, respectively, showing how parents socialize about ethnicity-race differently by child gender.…”
Section: Extent and Nature Of Ersmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychologists and family science scholars assert that various forms of oppression other than racism (e.g., heterosexism, nationalism, and colonialism) influences family socialization (Collins, 1998; David et al, 2017; Jordan, 2021). Additionally, research on Asian Americans' racial socialization similarly suggests that socialization is informed by various social identities, and Asian Americans learn about the implications of their racial, gender, and sexual identities in tandem (Ahn et al, 2021; Keum et al, 2023). Therefore, the broader framing of critical consciousness socialization gives voice to how family conversations about power can expand beyond analyses of racism.…”
Section: Introductionmentioning
confidence: 99%